REST suppression mediates neural conversion of adult human fibroblasts via microRNA‐dependent and ‐independent pathways. Issue 8 (23rd June 2017) - Drouin‐Ouellet, Janelle; Lau, Shong; Brattås, Per Ludvik; Rylander Ottosson, Daniella; Pircs, Karolina; Grassi, Daniela A; Collins, Lucy M; Vuono, Romina; Andersson Sjöland, Annika; Westergren‐Thorsson, Gunilla; Graff, Caroline; Minthon, Lennart; et al.
Abstract: Direct conversion of human fibroblasts into mature and functional neurons, termed induced neurons (iNs), was achieved for the first time 6 years ago. This technology offers a promising shortcut for obtaining patient‐ and disease‐specific neurons for disease modeling, drug screening, and other biomedical applications. However, fibroblasts from adult donors do not reprogram as easily as fetal donors, and no current reprogramming approach is sufficiently efficient to allow the use of this technology using patient‐derived material for large‐scale applications. Here, we investigate the difference in reprogramming requirements between fetal and adult human fibroblasts and identify REST as a major reprogramming barrier in adult fibroblasts. Via functional experiments where we overexpress and knockdown the REST‐controlled neuron‐specific microRNAs miR‐9 and miR‐124, we show that the effect of REST inhibition is only partially mediated via microRNA up‐regulation. Transcriptional analysis confirmed that REST knockdown activates an overlapping subset of neuronal genes as microRNA overexpression and also a distinct set of neuronal genes that are not activated via microRNA overexpression. Based on this, we developed an optimized one‐step method to efficiently reprogram dermal fibroblasts from elderly individuals using a single‐vector system and demonstrate that it is possible to obtain iNs of high yield and purity from aged individuals with a range of familial and sporadic neurodegenerative disorders including Parkinson's, Huntington's, as well as Alzheimer's disease. Synopsis: REST inhibition removes neuronal reprogramming barrier in adult dermal fibroblasts. The resulting high number of induced neurons from elderly patients allows for large scale biomedical applications such as disease modeling, drug screening and early and/or differential diagnostics. The most commonly used neural conversion genes Ascl1 and Brn2 elicit largely distinct transcriptional responses between fetal and adult fibroblasts. REST inhibition removes reprogramming barrier of adult fibroblasts. The effect of RESTi is only partially mediated via the neuron specific microRNAs miR‐9 and miR‐124 up‐regulation. In addition to activate a similar subset of neuronal genes as miR‐9 and miR‐124 overexpression, RESTi activates a distinct set of neuronal genes. An all‐in‐one conversion vector overexpressing Ascl1 and Brn2 and knocking down REST improves the reprogramming process and renders it suitable for biomedical applications. Abstract : REST inhibition removes neuronal reprogramming barrier in adult dermal fibroblasts. The resulting high number of induced neurons from elderly patients allows for large scale biomedical applications such as disease modeling, drug screening and early and/or differential diagnostics.